On-farm diversity and production challenges in Ethiopian tef [Eragrostis tef ((Zuccagni) Trotter)] landraces from Arsi zone, Ethiopia: Implications for breeding and conservation - Fekadu Gadissa; Muhamed Adem (Heliyon)
Context: Tef [Eragrostis tef ((Zucc.) Trotter)] is a remarkable indigenous crop, highly adaptive and resilient to erratic and extreme climatic and soil conditions. It is a major staple food in Ethiopia and is usually cultivated for household consumption and the generation of income. However, nowadays, the crop particularly, the landraces are exposed to genetic erosion owing to biotic and abiotic factors. Thus, detecting the current status and production bottlenecks of the crop is key to enhance its production and conservation. Objective: The main objectives of this study were to assess the extent of on-farm diversity, genetic erosion and current production challenges of Tef landraces in Arsi Zone, Oromia region, Ethiopia. Methods: The study was conducted in the Arsi zone, Southeast Ethiopia using 400 selected farmers. Data were collected using a semi-structured questionnaire and analyzed using Minitab version 19. The respondent farmers included the different sex groups, age groups, educational status, marital status, and religious outlooks. Results and conclusion: S: A total of 26 Tef landraces have been identified to be cultivated over the last 2 to 3 decades and/or still in production in the study areas. The respondents indicated differences in the landraces with regard to morphological features which along with the naming's could suggest their genetic distinctiveness. Patterns of on-farm diversity in the landraces showed a varied abundance in the area where eleven landraces showed a relatively higher estimate (D = 0.75 in Sergegna to D = 0.58 in Bulga). With the exception of Aruso Tef (D = 0.47), all the remaining landraces showed minimal or no (D = 0.00) genetic abundance. The extent of the Sorenson similarity index revealed a higher similarity (0.69 in Enkelo Wabe vs Arsi Robe to 0.77 in Shirka vs Arsi Robe) and the areas revealed a higher landrace richness (R) and evenness index (E). However, patterns of temporal genetic diversity and extent of genetic erosion revealed that only 10 are grown currently (combined genetic erosion of 61.54 %). In general, biotic and abiotic factors are challenging the current production of the crop in the area. Hence, researchers and all stakeholders should pay attention to conserving and breeding this important food crop. Significance: Understanding the extents of on-farm diversity and possible production challenges of the crop could facilitate and enhance its breeding, conservation and utilizations and hence, contribute to the food security of the country.